Biography: The Role of Jose Maceda in the Music Research Circle - Thiti Panya-in; Jarernchai Chonpairot; Manop Wisutthipat (Wacana Seni Journal of Arts Discourse, 2015)
Jose Maceda was an international figure among music scholars in Southeast Asia. He excelled in many fields, notably composition and research. This qualitative study aims at examining the philosophy, thought and working style of Jose Maceda and investigating the role of Jose Maceda in the music research circle of Southeast Asia. The researchers gathered fieldwork data from document analysis, interviews and observations with music scholars in The Philippines and in Thailand. Data was analysed in accordance with the given objectives and the results of the study are presented in a descriptive analysis form. Jose Maceda received his PhD in ethnomusicology from The University of California, Los Angeles. He was a pioneer in conducting research on ethnic music in The Philippines and Southeast Asia. His research works and compositions have been published and performed in many countries, such as Canada, Germany, Malaysia, Philippines, England and United States. He left his career as a pianist and concentrated on ethnomusicology. In 1997, Maceda established an information center for ethnic music at the University of the Philippines, collecting data of ethnic music in the Philippines and Southeast Asia. The role of Maceda is multi-dimensional: in music education, as a music scholar, in research, in musical anthropology and in establishing an ethnomusicology network. Results found that he trained many music teachers, in music education as well as in ethnomusicology, who became researchers of international reputation in their own right. He, along with other well known Asian ethnomusicologists, was a co-founder of the Asia Pacific Society for Ethnomusicology (APSE).